Corporate bonds and structured financial products - Choudhry, Moorad (Fixed income markets library, 2004)
This book is a detailed account of the instruments that are used in the corporate bond markets, from conventional "plain vanilla" bonds to hybrid instruments and structured products. There is background information on bond pricing and yield, as well as a detailed look at the yield curve. The book covers the full set of instruments used by companies to raise finance, and which are aimed at a wide range of investors.